Irrigation canals and reservoirs - Rice, C.E. (My University, 1897)
Introduction: The all important question to the modern farmer is that of water supply. In the eastern and southern states the annual rainfall is sufficient for all agricultural purposes and sometimes necessitates drainage, but in the more arid regions of the west the rainfall is not sufficient and the farmer must help nature in the struggle with drouth. By skillful use of the rainfall the arid deserts of Utah have become luxurious gardens, the valley of Colorado have become as productive as her mines, the endless stretch of buffalo grass in southwestern Kansas has changed to a green sea of alfalfa, and throughout the whole arid west the course of the canal is marked by prosperous homes. The subject of irrigation is too extensive for one person to thoroughly put forth in so limited an article, so only one phase of it will be discussed; irrigation canal and reservoirs.
Citation: Rice, C.E. Irrigation canals and reservoirs. Senior thesis, Kansas State Agricultural College, 1897.
Morse Department of Special Collections
Keywords: Water resources; Water supply; Irrigation; Reservoirs; Canals; Theses; Manuscripts (documents)